Cecropia pachystachya Leaves Present Potential to Be Used as New Ingredient for Antiaging Dermocosmetics. (3rd April 2019) - Fernandes, Maria Fernanda; Conegundes, Jessica Leiras Mota; Pinto, Nícolas de Castro Campos; Oliveira, Luiz Gustavo de; Aguiar, Jair Adriano Kopke de; Souza-Fagundes, Elaine Maria; Scio, Elita
Abstract : Several biological activities have been reported for leaf extracts of Cecropia pachystachya species, including antioxidant and wound healing activities. This study aims to report, for the first time, the antiaging potential of the hydroethanolic (HE) and the ethanolic (EE) extracts obtained from the leaves of C. pachystachya using different in vitro assays. Both HE and EE presented relevant antioxidant capacity in different models, including phosphomolybdenum, 1, 1-diphenyl-2-picryl-hydrazyl (DPPH), carotene/linoleic acid bleaching, and thiobarbituric acid reactive substances (TBARS) assays. Their ability to prevent the production of advanced glycation end products (AGEs) was also evaluated, and both extracts showed important activity, especially HE. The extracts also stimulated the fibroblasts proliferation in vitro, specialized cells that produce several mediators which maintain the skin integrity and youthfulness. Cytotoxicity of the extracts was not observed for this lineage or HEK-293, human embryonic kidney cells widely used to evaluate cytotoxicity of chemical compounds. HE also exhibited the ability to inhibit the collagenase (metalloproteinase MMP-2) and elastase activities. The total phenolic and flavonoids contents were also determined. HPLC analysis revealed the presence of the flavonoids orientin and iso-orientin, which were quantified to be used as chemical markers. The results suggested that the extracts of C. pachystachya leaves present the potential to be used in dermocosmetic formulations to prevent the skin aging process, which attracts the attention of pharmaceutical companies and researchers interested in the development of novel ingredients likely to be used as active principles in antiaging products.